EFFECTIVE MANAGEMENT: A RECIPE FOR ATTAINING THE GOALS OF NOMADIC EDUCATION PROGRAMME IN NIGERIA - Mahmud, Abbas (Sokoto Educational Review, 2013)
The paper examined different areas of management in relation to Nomadic Education programme and looked into policy statement which is enshrined in the National Policy on Education and definition regarding to management. System theory was also used in order to examine issues o f effective management in schools. Administrators roles in schools was discussed such as mutual respect, shared ideas and the process in establishing nomadic schools with a lot of considerations before erecting the structure. School plant planning was discussed in respect of managers/head teachers in managing the schools toward the achieving educational goals. The paper also examined the component that helps in achieving the goals which are management structure, the hierarchical model to the management o f nomadic schools and how it will really help in managing the school activities. Lastly the paper made some recommendations, such as, government should provide the needed teaching and learning materials for successful attaining goals etc.